Draft Annual Plan 1994-95 Andhra Pradesh Volume-I (General) - Planning Commission (Planning Commission, 1994)
Andhra Pradesh, with a population of 6.65 crores as per 1991 census is the fifth most populous state in the country. The decadal growth rate of the state 24.2 is higher than all India average of 23.5. About 73 percent of the state's population live In rural areas. the work participation rate in the State as per 1991 Census at 45% is way ahead of the all India average of 38%.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh